2013
DOI: 10.1007/s40266-013-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Pharmacotherapy in Elderly Primary Care Patients Through Medication Reviews: A Randomised Controlled Study

Abstract: Medication reviews involving pharmacists in primary health care appear to be a feasible method to reduce the number of patients with PIMs, thus improving the quality of pharmacotherapy in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
182
4
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(209 citation statements)
references
References 37 publications
17
182
4
5
Order By: Relevance
“…The tendency for the prevalence in the use of psychiatric drugs is observed to rise according to subjects' age range. (11) Such finding corroborates the results found in this study. Thus, the analysis of data showed that the lower prevalence in the use of psychiatric drugs was found for the age range between 18 to 40 years (10.1%), followed by persons between 41 and 59 years of age (31.6%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The tendency for the prevalence in the use of psychiatric drugs is observed to rise according to subjects' age range. (11) Such finding corroborates the results found in this study. Thus, the analysis of data showed that the lower prevalence in the use of psychiatric drugs was found for the age range between 18 to 40 years (10.1%), followed by persons between 41 and 59 years of age (31.6%).…”
Section: Discussionsupporting
confidence: 91%
“…Notwithstanding, there is evidence that making use of more than one drug is common among psychiatric drug users. (6,11) Such aspect is particularly important, once those patients have higher risks of suffering from adverse effects and drug interactions. (2,11) The association between psychiatric drugs and Common Mental Disorders, revealed in this study, is confirmed by previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of MTPs identified in this study is a little lower than the rates identified in studies on elderly [23,27,[37][38][39], and much lower than the 8.2 MTPs per person identified in an Australian study on community-dwelling people with mental illnesses [40]. The Australian study used a different categorization of MTPs with a large number of subcategories, which will increase the number of MTPs.…”
Section: Discussionmentioning
confidence: 60%
“…In Sweden, developed and implemented interventions include: the development of national quality prescribing indicators (256); the education of healthcare professionals to geriatric pharmacology and the creation of regional recommendations for drug therapy in the elderly by the Drug and Therapeutic Committees; computerised decision support systems (257); medication review in primary care and nursing homes (258,259); medication reconciliation at hospital discharge (260) and pharmacist-based interventions (261). Moreover, the Swedish government has provided financial incentives that award counties achieving performance targets for certain local prescribing indicators (262).…”
Section: Discussionmentioning
confidence: 99%